On the taxonomic status of the genus Thrasyopsis (Poaceae, Panicoideae, Paspaleae): new combinations in Paspalum - Rua, Gabriel H.; Valls, José Francisco M. (Phytotaxa, 2012)
The two species formerly assigned to the genus Thrasyopsis are transferred to Paspalum, on the basis of morphological and molecular evidence. The new combinations Paspalum rawitscheri and P. repandum are published.